A lagrangian curvilinear finite element - Kaiser, T. M. V.; Elwi, A. E.; Mioduchowki, A. (European Journal of Computational Mechanics, 1994)
A total lagrangian formulation is developed in terms of a general orthogonal curvilinear coordinate system. The formulation is used to develop an axisymmetric finite element in cylindrical coordinates to mode/large displacement nonlinerarities arising out of large non-axisymmetric displacements. An axisymmetric shell under asymmetric loads and an axisymmetric beam-column are modelled to demonstrate this capability.